Candida sepsis from local infection in a patient with a urostomy on SGLT2 inhibitor therapy. (September 2020) - Wendt, Ralph; Schmerler, Diana; Müller-Hechler, Charlotte; Weichold, Christian; Craatz, Diana; Beige, Joachim
Abstract: Sodium–glucose co-transporter 2 (SGLT2) inhibitors exhibit impressive cardio-renal benefits in patients with a high cardiovascular risk. Genital yeast infections are important side effects of this class of drugs. We report a case of Candida glabrata sepsis secondary to a Candida infection of the urostomy of a patient on SGLT2 inhibitor therapy. In urostomy patients, one should critically evaluate the risk of mycotic infections against the cardiovascular and glycaemic benefits of SGLT2 inhibition. Urostomy patients without a high cardiovascular risk should not be treated with SGLT2 inhibitors.